ANALISIS ENERGY SECURITY BERDASARKAN AWARENESS ENERGY TERHADAP PRODUKTIVITAS ENERGI PADA PABRIK PALM KERNEL OIL PT. PERKEBUNAN NUSANTARA V TANDUN ROKAN HULU - Singh, Malkit; Daulay, Iwan Naulai; ', Samsir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the level of energy security based on awareness energy is done in the Palm Kernel Oil Plant Tandun PT. PTPN V. By using Slovin formula, the number of samples taken in the amount of 66 respondents who are all employees of the factory. Data was taked by giving them the questionaires and descriptive analysis methods was chosen for data analiysis by SPSS version 17.0. These results indicate that the energy security is based on energy awareness is quite awareness and saving on energy productivity at the Palm Kernel Oil Plant Tandun PT. PTPN V. From the research result company should further improve biogas and minimize diesel consumption.Keywords: energy security, energy awareness, and productivity energy.